Genital herpesvirus hominis infection in mice. I. Development of an experimental model. - Overall, J C (1975)
Pregnant female mice, after intravaginal inoculation with Herpesvirus hominis (HVH) type 2, developed vaginitis on days 5 to 7 after virus challenge, followed by hunching and hind limb paralysis on days 7 to 9 and death from encephalitis on days 9 to 11. After initial replication in the mucous membranes of the genital tract, virus spread to the spinal cord and ascended to involve the brain. Viremia or replication of H. hominis type 2 in the liver or spleen was not detected. Virus was cleared from vaginal secretions by days 8 to 10 after infection. Pregnant mice were more susceptible to the infection than nonpregnant mice. This experimental infection in female mice provides a model for genital herpesvirus infection and for herpesvirus infection and for herpesvirus encephalitis in which one can evaluate potentially promising antiviral chemotherapeutic agents.